Increased Stiffness of the Superficial Cervical Extensor Muscles in Patients With Cervicogenic Headache: A Study Using Shear Wave Elastography - Lin, Li-Zhen; Yu, Yan-Ni; Fan, Jie-Cheng; Guo, Pei-Wu; Xia, Chun-Feng; Geng, Xue; Zhang, Shu-Yun; Yuan, Xiang-Zhen (Frontiers in Neurology, 2022)
Background Cervicogenic headache (CEH) is a secondary headache caused by lesions of the cervical spine and surrounding soft tissues. Cervical muscle dysfunction may be related to the onset of CEH. However, whether cervical muscle stiffness changes in patients with CEH has not been well studied. The purpose of this study was to explore changes in superficial cervical extensor muscle stiffness in patients with CEH using shear wave elastography (SWE). Methods In this study, 19 patients with CEH and 20 healthy controls were recruited. Superficial cervical extensor muscle stiffness was obtained from SWE, and the SuperLinear SL10-2 MHz linear array probe in the musculoskeletal muscle mode was chosen as the transducer. Regions of interest in the trapezius (TRAP), splenius capitis (SPL), semispinalis capitis (SCap), and semispinalis cervicis (SCer) were manually segmented. Correlations between superficial cervical extensor muscle stiffness and visual analog scale (VAS) scores, age, and body mass index (BMI) were analyzed using Pearson's correlation. Receiver operating characteristic (ROC) curve was used to investigate the diagnostic ability of superficial cervical extensor stiffness for CEH. Results Superficial cervical extensor muscle stiffness on the headache side of patients with CEH was higher than that on the non-headache side and in healthy controls (p < 0.05). Increased stiffness was also observed in SCer on the non-headache side of patients with CEH compared to healthy controls (p < 0.01). In patients with CEH, SCer stiffness was positively correlated with VAS scores (r = 0.481, p = 0.037), but no correlation was found between other muscles and VAS scores (p > 0.05). The areas under the curve of TRAP, SPL, SCap, and SCer in diagnosing CEH were 0.766, 0.759, 0.964, and 1.000, respectively. Conclusions Increased stiffness was observed in the superficial cervical extensor muscles on the headache side of patients with CEH. SCer stiffness was correlated with headache intensity in patients with CEH and may provide clues for the diagnosis of CEH.